UMP researchers develop SCAV self-driving bus for campus residents - Mimi Rabita, Abdul Wahit (2021)
With various expertise in the engineering and technology field, researchers from Universiti Malaysia Pahang (UMP) are currently developing a smart bus with a computer system to move on its own without a driver (self-driving).